Effectiveness test of microfilter mask based on straw waste cellulose fiber biopolymer - Rofiqoh, Hazi; Ummah, Baiq Hizanatul; Hanafi, Imam Galih; Budhiartini, Baiq Nely; Murniati, Murniati; Chen, Chang-Nan (Acta Chimica Asiana, 2025)
Straw waste, which is often underutilized, contains abundant cellulose that holds potential as a raw material for environmentally friendly filtration technologies. The conversion of agricultural waste into value-added products, such as mask microfilters, aligns with the increasing demand for sustainable materials, particularly in the context of public health protection. Harnessing cellulose from straw offers a promising alternative to synthetic fibers commonly used in mask production, while simultaneously addressing waste management challenges. This study aims to determine the characterization of microfilter masks from straw waste and the effectiveness of straw microfilters used in cloth masks. Cellulose from straw waste can be used as a mask microfilter by going through several stages, such as: preparation, extraction, delignification, bleaching, characterization, and making mask microfilters and effectiveness tests. The characterization of structure, morphology and topology from the straw waste cellulose has not been fully degraded from lignin as shown from the aromatic C = C stretching vibrations on lignin at wave numbers 1638.34 cm-1, 1648 cm-1, and 1583.56 cm-1 of FTIR also SEM tools at 3600 times magnification. The effectiveness of the microfilter mask is 94% and 91% as evidenced by each bacterial filtration test and the decreasing data of the dust filtration test.